A highly directive graphene antenna embedded inside a Fabry-Perot cavity in terahertz regime. (May 2018) - Roshanaei, Majid; Karami, Hamidreza; Dehkhoda, Parisa; Esfahani, Hamid; Dabir, Fatemeh
Abstract: In this paper, a highly directive nano-thickness graphene-based antenna is introduced in the terahertz frequency band. The antenna is a graphene patch dipole which is placed between two Bragg mirrors called Fabry-Perot cavity. Tunability of the graphene's conductivity makes it possible to excite the desired resonances of the cavity. Here, first, a single resonant antenna is introduced at 5 THz with an enhanced gain from 2.11 dBi to 12.8 dBi with a beamwidth of 22.7°. Then, a triple resonant antenna at 4.7, 5 and 5.3 THz is presented with respective gains of 7.97, 11.9 and 8.52 dBi. Finally, the effect of dimensions and number of the dielectric layers of the cavity are studied in order to further increase in directivity. Highlights: A highly directive tunable antenna based on graphene is investigated. The directivity of the proposed antenna is enhanced about 10.7 dB. A triple resonant highly directive antenna at 4.7, 5 and 5.3 THz are designed. The effect of number of dielectric layers in the cavity is studied.